2008
DOI: 10.1016/j.ccr.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Abnormal Proliferation by Nonmyelinating Schwann Cells Triggers Neurofibroma Formation

Abstract: Recent evidence suggests that alterations in the self-renewal program of stem/progenitor cells can cause tumorigenesis. By utilizing genetically engineered mouse models of neurofibromatosis type 1 (NF1), we demonstrated that plexiform neurofibroma, the only benign peripheral nerve sheath tumor with potential for malignant transformation, results from Nf1 deficiency in fetal stem/progenitor cells of peripheral nerves. Surprisingly, this did not cause hyperproliferation or tumorigenesis in early postnatal period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 51 publications
4
143
0
1
Order By: Relevance
“…Interestingly, it has been suggested that the induction of abnormal proliferation of nmSC triggers neurofibroma formation. In Nf1 flox/Ϫ ;P0A-cre ϩ mice, Zheng et al (2008) have shown that Nf1 deficiency does not cause hyperproliferation or tumorigenesis during the early postnatal period. The only differential trait found at this time is the existence of abnormal Remak bundles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been suggested that the induction of abnormal proliferation of nmSC triggers neurofibroma formation. In Nf1 flox/Ϫ ;P0A-cre ϩ mice, Zheng et al (2008) have shown that Nf1 deficiency does not cause hyperproliferation or tumorigenesis during the early postnatal period. The only differential trait found at this time is the existence of abnormal Remak bundles.…”
Section: Discussionmentioning
confidence: 99%
“…We also show that overexpression of SMDF provokes a dramatic proliferation of nmSC, suggesting that neuregulin is an in vivo mitogenic signal for these cells. Akin to type I neurofibromatosis (Ling et al, 2005;Zheng et al, 2008), mutant nerves show increased deposits of collagen fibrils in the extracellular space and, in some cases, develop big tumors, suggesting that neuregulin overexpression in the small-sized axons of Remak bundles could be involved in the development of neurofibroma and other peripheral nerve tumors.…”
Section: Introductionmentioning
confidence: 99%
“…During development, neural-crest cells migrate along the peripheral nerves, and a subset of cells commit to the Schwann cell lineage. Zheng and colleagues demonstrated that plexiform neurofibromas could originate from Nf1 deficiency in fetal nonmyelinating Schwann cells (4). Le and colleagues identified a population of progenitor cells residing in the dermis, termed "skin-derived precursors" that form dermal neurofibromas through loss of Nf1 (5).…”
Section: Introductionmentioning
confidence: 99%
“…In NF1 tumorigenesis, the question whether these tumors arise from neural crest stem cells or differentiates glia remains very controversial (4,5,16,17). In this regard, we have previously shown a dedifferentiation of Schwann cells, as well as an activation of the Hedgehog signaling pathway, during malignant transformation of plexiform neurofibromas (18).…”
Section: Introductionmentioning
confidence: 99%
“…In other tissular context, targeting astrocytoma-associated oncogenic lesions to the nervous system progenitors results in tumour development, whereas targeting them to the zone containing just differentiated cells only gives rise to local astrogliosis (Alcantara Llaguno et al, 2009). In all these and other similar cases (Dirks, 2008;Joseph et al, 2008;Zheng et al, 2008) it is therefore clear that the initiating event must take place in a stem cell, even if, afterwards, the macroscopic tumour is composed by differentiated cells. This indicates a pathological direct reprogramming mediated by the oncogenic lesions.…”
Section: Cancer: the Dark Side Of Plasticitymentioning
confidence: 99%